Upaya Pembuatan Cashew Nut Shell Liquid Sebagai Bahan Baku Produk Farmasi: Efforts to Make Cashew Nut Shell Liquid as Raw Material for Pharmaceutical Products - Maria Saena Puru; Nur Masyithah Zamruddin; Niken Indriyanti (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Cashew (Anacardium occidentale L) is one of the plantation commodities which has a high economic value. However, the utilization is still limited to the cashew, while the shells have not been used as a product. The purpose of this study was to obtain cashew nut shell liquid (CNSL) oil from cashew nut shells. Furthermore, efforts were made to purify CNSL which could be used as an opportunity for the use of cashew nut shell oil in the pharmaceutical field. This research was conducted experimentally with the Soxhlet extraction method using n-hexane solvent and concentrated using a rotary evaporator. The analysis carried out included yield, viscosity, acid number, specific gravity and pH while the analysis of CNSL purification efforts included screening, management and use of ice cubes. The results obtained were yield (%) 29.76 ? 4.133, acid number (mg KOH / gr) 129.70 ? 10.927, specific gravity (g / ml) 1.086 ? 0.0009, viscosity (cps) 464.79 ? 42.959 and pH 6.13 ? 0.134. The way of purification efforts carried out by physical processes, use, use of ice cubes did not show significantly different results. It can be said that cashew nut shell oil can be used as raw material for pharmaceutical products from the amount of oil yield obtained and requested in the next research to find out more suitable methods for CNSL purification.